2010
DOI: 10.1007/s11274-010-0578-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylotype diversity in a benthic cyanobacterial mat community on King George Island, maritime Antarctica

Abstract: Cyanobacterial 16S ribosomal RNA gene diversity was examined in a benthic mat on Fildes Peninsula of King George Island (62º09'54.4''S, 58º57'20.9''W), maritime Antarctica. Environmental DNA was isolated from the mat, a clone library of PCR-amplified 16S rRNA gene fragments was prepared, and amplified ribosomal DNA restriction analysis (ARDRA) was done to assign clones to seven groups. Low cyanobacterial diversity in the mat was suggested in that 83% of the clones were represented by one ARDRA group. DNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…not using commercial kits) were used in the majority of studies (e.g. Callejas et al 2011;Barberan & Casamayor 2014;Mao et al 2014) DNA in a number of studies, but only twice since 2014 (Merlin et al 2014;Wasaki et al 2015).…”
Section: Summary Of Dna Extraction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…not using commercial kits) were used in the majority of studies (e.g. Callejas et al 2011;Barberan & Casamayor 2014;Mao et al 2014) DNA in a number of studies, but only twice since 2014 (Merlin et al 2014;Wasaki et al 2015).…”
Section: Summary Of Dna Extraction Methodsmentioning
confidence: 99%
“…Pansu et al 2015b) or biofilm samples (Callejas et al 2011;Zimmermann et al 2015; see Table S3 in Supplementary Material). These water column studies targeted a broad range of taxa including prokaryotes (e.g.…”
Section: Study Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Table S2), the specific organisms present in a mat may vary considerably. Certain groups are regularly detected in Antarctic mats: Cyanobacteria , particularly members of the Oscillatoriales such as Leptolyngbya and Phormidium , and the Nostocales (Taton et al ., ; Jungblut et al ., ; Taton et al ., ; Fernández‐Valiente et al ., ; Sutherland, ; Borghini et al ., ; Verleyen et al ., ; Anderson et al ., ; Callejas et al ., ; Fernandez‐Carazo et al ., ), Proteobacteria , the CFB group, Actinobacteria , and Firmicutes (Brambilla et al ., ; Van Trappen et al ., ; Peeters et al ., ; Antibus et al ., ; Varin et al ., ). Less commonly reported are Deinococcus‐Thermus , Planctomycetes , Verrucomicrobiales , and others (Brambilla et al ., ; Antibus et al ., ; Peeters et al ., ; Varin et al ., ).…”
Section: Antarctic Lakesmentioning
confidence: 99%
“…As in the present study, the cyanobacteria genes aligned to freshwater polar strains (Jungblut et al ., 2010). In another study of benthic mat samples from the Antarctic Peninsula, it was also shown that the recovered cyanobacterial diversity matched closely to other Antarctic terrestrial cyanobacteria (Callejas et al ., 2011).…”
Section: Primers Used In This Studymentioning
confidence: 60%